Tuturan Ritual Songgo Kamba pada Masyarakat Kecamatan Lobalain Kabupaten Rote Ndao - Ona Diana Bani; Ronni Marthen Ndun (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2021)
The purpose of this study is to identify, interpret and describe in order to provide an objective picture of the meaning and function contained in the ritual speech of songgo kamba in the people of Lobalain District, Rote Ndao Regency. This study uses cultural linguistic theory and qualitative descriptive methods. The songgo kamba ritual is a form of ritual for the people of Rote Ndao Regency to ask for protection and strength and health, especially for the cattle in the form of buffalo during the process of cultivating the fields. This ceremony is led by a mana songgo and is carried out in the uma lai section of the traditional house (the second stage of the traditional house). The songgo kamba ritual should not be done arbitrarily because this ritual is very sacred for the people of Rote.